Influence of chemical components La and heat treatment on the microstructure and mechanical property of AlSi₇Mg aluminum alloy - Yongyue Liu (Functional Materials, 2018)
The effect of La additives on aluminum alloy AlSi₇Mg and the casting temperature on its microstructure and mechanical properties was studied. It has been found that the addition of La has a significant improvement in the structure of the aluminum alloy and has a large effect on tensile strength and percentage elongation. When the La content was 0.2%, the sample property was the best. With increasing solution temperature, the grain size of the samples increased, the spherical coefficient decreased, the density decreased, and the mechanical properties deteriorated. When the temperature of the solution was 540° C, the microstructure and mechanical properties of the samples were the best. This indicates that the proper addition of chemical components and the control of the temperature of the solution can improve the properties of the aluminum alloy billet.